Low-smoke halogen-free flame-retardant XPE foam and preparation method thereof

CN122941075APending Publication Date: 2026-10-20HONGZHIDA PACKING (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129802.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]添加型无卤阻燃体系在聚烯烃材料中已有应用,但无机阻燃剂、磷氮类阻燃剂与非极性聚烯烃基体之间相容性有限,较高添加量容易导致团聚、熔体压力升高、泡孔破并、发泡倍率下降或压缩性能劣化

Benefits of technology

[0030]1、本发明采用外表面磷酸酯-硅氧烷改性镁铝水滑石,采用外表面改性镁铝水滑石、二乙基次膦酸铝、三聚氰胺聚磷酸盐、哌嗪聚磷酸盐、硼酸锌和含羟基硅树脂构成的六组分复合低烟无卤阻燃体系,采用低密度聚乙烯、乙烯-醋酸乙烯酯共聚物和聚烯烃弹性体构成三元聚烯烃基体;采用马来酸酐接枝聚乙烯作为相容剂,并在阻燃母粒阶段先对层状阻燃协效剂进行预分散,采用分步投料、末段加入过氧化二异丙苯、预交联和连续发泡相匹配的工艺窗口;外表面磷酸酯-硅氧烷改性镁铝水滑石能够改善层状无机颗粒与聚烯烃基体之间的界面结合,降低无机颗粒团聚对泡孔形成的不利影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention discloses a low-smoke halogen-free flame-retardant XPE foam and its preparation method, relating to the field of polymer foaming materials technology. The low-smoke halogen-free flame-retardant XPE foam is formed by chemical cross-linking and foaming of a polyolefin matrix resin, maleic anhydride-grafted polyethylene compatibilizer, composite low-smoke halogen-free flame retardant, azodicarbonamide foaming agent, dicumyl peroxide cross-linking agent, zinc oxide, zinc stearate, antioxidant, and polyethylene wax. The polyolefin matrix resin is composed of low-density polyethylene, ethylene-vinyl acetate copolymer, and polyolefin elastomer. This invention improves flame retardant and low-smoke performance while maintaining the closed-cell structure and processing stability of the XPE foam through the combination of an externally modified layered flame-retardant synergist, a composite low-smoke halogen-free flame-retardant system, a maleic anhydride-grafted polyethylene compatibilizer, and a continuous foaming process window.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer foaming materials technology, specifically to a low-smoke, halogen-free flame-retardant XPE foam and its preparation method. Background Technology

[0002] XPE foam is typically made primarily of polyethylene resin, combined with foaming agents, crosslinking agents, and processing aids, and is formed into a closed-cell foam material through extrusion calendering, crosslinking, and foaming. This type of material is characterized by its light weight, cushioning, thermal insulation, moisture resistance, and ease of composite processing, and can be used in applications such as floor mats, building insulation, packaging cushioning, transportation interiors, and electronic product cushioning.

[0003] As applications in construction, transportation, electronics, and new energy demand higher standards for material safety, smoke release, and environmental protection, XPE foam, in addition to maintaining a closed-cell structure, compression recovery, and processing stability, also needs to exhibit low flame propagation tendency and low smoke production tendency during combustion. Halogenated flame retardants or halogenated antimony synergistic systems can improve the flame retardancy of some materials, but there is still room for further improvement in the areas of low smoke and halogen-free materials.

[0004] Additive halogen-free flame retardant systems have been used in polyolefin materials, but the compatibility between inorganic flame retardants, phosphorus and nitrogen flame retardants and non-polar polyolefin matrices is limited. Higher addition amounts can easily lead to agglomeration, increased melt pressure, cell collapse, decreased foaming ratio, or deterioration of compression performance.

[0005] Among the existing publicly available technologies, there are solutions such as flame retardant systems for XPE sheets, layered bimetallic hydroxide flame retardants and smoke suppressants, and halogen-free flame retardant polyethylene foam materials. However, for chemically cross-linked continuous foaming XPE systems, a better comprehensive balance needs to be achieved between flame retardant dispersion, charring and smoke suppression, closed-cell foaming, degree of cross-linking, and continuous processing stability. Summary of the Invention

[0006] The purpose of this invention is to provide a low-smoke, halogen-free flame-retardant XPE foam and its preparation method, which achieves flame-retardant and low-smoke performance, closed-cell foam structure, processing stability and mechanical properties without using bromine-based flame retardants, chlorine-based flame retardants and antimony trioxide.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A low-smoke, halogen-free, flame-retardant XPE foam is formed by chemical cross-linking and foaming of raw materials comprising the following components, based on 100 parts by weight of a polyolefin matrix resin:

[0009] 100 parts by weight of polyolefin matrix resin, 4-7 parts by weight of maleic anhydride grafted polyethylene compatibilizer, 24-34 parts by weight of composite low-smoke halogen-free flame retardant, 8-13 parts by weight of azodicarbonamide foaming agent, 1.1-2.2 parts by weight of dicumyl peroxide crosslinking agent, 1-3 parts by weight of zinc oxide, 0.3-1.2 parts by weight of zinc stearate, 0.1-0.5 parts by weight of antioxidant, and 0.2-0.8 parts by weight of polyethylene wax;

[0010] The polyolefin matrix resin is composed of low-density polyethylene, ethylene-vinyl acetate copolymer and polyolefin elastomer, wherein the low-density polyethylene is 65-78 parts by weight, the ethylene-vinyl acetate copolymer is 12-22 parts by weight, and the polyolefin elastomer is 5-15 parts by weight, totaling 100 parts by weight.

[0011] The composite low-smoke halogen-free flame retardant is composed of phosphate ester-siloxane modified magnesium aluminum hydrotalcite, aluminum diethylphosphinate, melamine polyphosphate, piperazine polyphosphate, zinc borate, and hydroxyl-containing silicone resin on the outer surface.

[0012] Based on a mass of 100wt% of the composite low-smoke halogen-free flame retardant, the outer surface phosphate-siloxane modified magnesium aluminum hydrotalcite comprises 34-40wt%, aluminum diethylphosphinate comprises 28-34wt%, melamine polyphosphate comprises 12-16wt%, piperazine polyphosphate comprises 9-13wt%, zinc borate comprises 4-7wt%, and hydroxyl-containing silicone resin comprises 2-5wt%.

[0013] The phosphate-siloxane modified magnesium aluminum hydrotalcite on the outer surface is obtained by surface treatment of magnesium aluminum hydrotalcite, phosphorus-containing silane coupling agent and γ-aminopropyltriethoxysilane in a mass ratio of 100:1.5-4.0:0.5-2.5.

[0014] The composite low-smoke halogen-free flame retardant does not contain polyphosphate intercalated magnesium aluminum hydrotalcite, bromine-based flame retardants, chlorine-based flame retardants, or antimony trioxide.

[0015] The density of the low-smoke halogen-free flame-retardant XPE foam is 40-70 kg / m³. 3 The average pore size is 120–240 μm, the gel content is 35–60%, and the closed-cell rate is 88–98%.

[0016] Furthermore, the density of the low-density polyethylene is 0.916–0.925 g / cm³. 3The melt flow rate is 0.5–4.0 g / 10 min, and the test conditions are 190℃ and 2.16 kg; the vinyl acetate structural unit content in the ethylene-vinyl acetate copolymer is 12–20 wt%, the melt flow rate is 1.0–6.0 g / 10 min, and the test conditions are 190℃ and 2.16 kg; the polyolefin elastomer is an ethylene-octene copolymer elastomer with a density of 0.865–0.885 g / cm³. 3 The melt flow rate was 0.5–5.0 g / 10 min, and the test conditions were 190 °C and 2.16 kg.

[0017] Furthermore, the maleic anhydride grafting rate of the maleic anhydride-grafted polyethylene compatibilizer is 0.6–1.8 wt%, the acid value is 6–18 mg KOH / g, the melt mass flow rate is 1.0–8.0 g / 10 min, and the test conditions are 190 °C and 2.16 kg.

[0018] Furthermore, the outer surface phosphate-siloxane modified magnesium aluminum hydrotalcite has a D50 particle size of 0.8–3.5 μm, a D90 particle size of no more than 8 μm, and a magnesium-aluminum molar ratio of 2.0–3.5:1; the aluminum diethylphosphinic acid has a D50 particle size of 1.0–6.0 μm, the melamine polyphosphate has a D50 particle size of 2.0–8.0 μm, and the zinc borate has a D50 particle size of 1.0–5.0 μm; the hydroxyl-containing silicone resin has a number-average molecular weight of 800–6000 and a hydroxyl value of 30–120 mg KOH / g.

[0019] Furthermore, the thickness of the low-smoke halogen-free flame-retardant XPE foam is 1.0–12 mm, and the foaming ratio is 8–28 times; the antioxidant is a combination of hindered phenolic antioxidant and phosphite antioxidant, with a mass ratio of 1:0.5–2; the D50 particle size of the azodicarbonamide foaming agent is 4–12 μm, and the decomposition peak temperature is 180–210 °C.

[0020] Furthermore, the low-smoke halogen-free flame-retardant XPE foam is suitable for XPE sheets, rolls, or composite foams that require low-smoke halogen-free flame retardancy, closed-cell insulation, and composite processability.

[0021] This invention also provides a method for preparing the above-mentioned low-smoke halogen-free flame-retardant XPE foam, comprising the following steps:

[0022] S1, External Surface Modification: Magnesium aluminum hydrotalcite is dispersed in an ethanol-water mixed solvent, a phosphorus-containing silane coupling agent is added for the first surface treatment, and then γ-aminopropyltriethoxysilane is added for the second surface treatment. After filtration, washing and drying, phosphate ester-siloxane modified magnesium aluminum hydrotalcite is obtained.

[0023] S2, Preparation of flame retardant masterbatch: The magnesium aluminum hydrotalcite with phosphate ester-siloxane modified on the outer surface obtained in step S1 is mixed with a portion of maleic anhydride grafted polyethylene compatibilizer, and then aluminum diethylphosphinate, melamine polyphosphate, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin are added and mixed again, granulated, to obtain flame retardant masterbatch.

[0024] S3, Preparation of XPE foam masterbatch: Low-density polyethylene, ethylene-vinyl acetate copolymer, polyolefin elastomer, remaining maleic anhydride grafted polyethylene compatibilizer and flame retardant masterbatch obtained in step S2 are added to an extrusion device for plasticizing and mixing. Then, azodicarbonamide foaming agent, zinc oxide, zinc stearate, antioxidant and polyethylene wax are added. Finally, dicumyl peroxide crosslinking agent is added, and the mixture is extruded and calendered to obtain XPE foam masterbatch.

[0025] S4, Pre-crosslinking and continuous foaming: The XPE foam master sheet obtained in step S3 is pre-crosslinked at 150-172°C for 1-4 min, then continuously foamed at 195-222°C for 1-5 min, and cooled and shaped to obtain the low-smoke halogen-free flame-retardant XPE foam.

[0026] Further, in step S1, the mass ratio of ethanol to water in the ethanol-water mixed solvent is 60-90:10-40, the solid content of magnesium aluminum hydrotalcite in the ethanol-water mixed solvent is 10-35 wt%, and the pH of the system is 4.5-6.5; the mass ratio of magnesium aluminum hydrotalcite, phosphorus-containing silane coupling agent, and γ-aminopropyltriethoxysilane is 100:1.5-4.0:0.5-2.5; the temperature of the first surface treatment is 50-75℃, and the time is 0.5-2h; the temperature of the second surface treatment is 55-85℃, and the time is 1-4h; the drying temperature is 80-105℃, and the drying time is 3-10h.

[0027] Further, in step S2, the phosphate-siloxane modified magnesium aluminum hydrotalcite with an outer surface is first mixed with a portion of maleic anhydride-grafted polyethylene compatibilizer at 110–130°C for 2–5 min, then diethylphosphinate aluminum, melamine polyphosphate, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin are added, and the mixture is further mixed at 115–140°C for 3–8 min. After granulation, the moisture content of the flame retardant masterbatch is controlled below 0.12 wt%. In step S3, the barrel temperature of the extrusion equipment is 95–120°C, the melt pressure is 6–15 MPa, the calender roll temperature is 30–65°C, and the thickness of the XPE foam masterbatch is 0.5–5.0 mm. In step S4, the linear speed of the continuous foaming furnace is 2–8 m / min.

[0028] Furthermore, after foaming, the foam undergoes curing at 50–90°C for 2–8 hours, followed by one or more post-treatments including cutting, winding, slicing, embossing, hot pressing, adhesive bonding, corona treatment, or plasma treatment; the resulting low-smoke halogen-free flame-retardant XPE foam has a density of 40–70 kg / m³. 3 The average pore size is 120–240 μm, the gel content is 35–60%, and the closed-cell rate is 88–98%.

[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0030] 1. This invention employs a six-component composite low-smoke halogen-free flame retardant system composed of externally surface-modified magnesium aluminum hydrotalcite, aluminum diethylphosphinate, melamine polyphosphate, piperazine polyphosphate, zinc borate, and hydroxyl-containing silicone resin. The ternary polyolefin matrix is ​​composed of low-density polyethylene, ethylene-vinyl acetate copolymer, and polyolefin elastomer. Maleic anhydride-grafted polyethylene is used as a compatibilizer, and the layered flame retardant synergist is pre-dispersed in the flame retardant masterbatch stage. A process window matching stepwise feeding, final addition of dicumyl peroxide, pre-crosslinking, and continuous foaming is employed. The externally surface-modified magnesium aluminum hydrotalcite improves the interfacial bonding between layered inorganic particles and the polyolefin matrix, reducing the adverse effects of inorganic particle agglomeration on cell formation.

[0031] 2. This invention utilizes aluminum diethylphosphinate, melamine polyphosphate, and piperazine polyphosphate to form a phosphorus-nitrogen flame retardant and char-forming system; zinc borate and hydroxyl-containing silicone resin can improve the inorganic nature and barrier properties of the combustion residue layer; magnesium aluminum hydrotalcite can exert a synergistic effect of heat absorption, dilution, barrier, and smoke suppression; maleic anhydride-grafted polyethylene can improve the dispersion of the flame retardant system in polyolefins; through the combination of the above components and processes, the resulting foam can achieve a good balance between flame retardancy, low smoke, closed-cell structure, foaming ratio, and compression recovery. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 This is a process flow diagram for the preparation of the low-smoke halogen-free flame-retardant XPE foam of the present invention. Detailed Implementation

[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] In the embodiments of this specification, low-density polyethylene is abbreviated as LDPE, ethylene-vinyl acetate copolymer is abbreviated as EVA, polyolefin elastomer is abbreviated as POE, maleic anhydride grafted polyethylene compatibilizer is abbreviated as PE-g-MAH, magnesium aluminum hydrotalcite is abbreviated as MgAl-LDH, phosphate ester-siloxane modified magnesium aluminum hydrotalcite is abbreviated as modified MgAl-LDH, aluminum diethylphosphinate is abbreviated as AlPi, melamine polyphosphate is abbreviated as MPP, azodicarbonamide foaming agent is abbreviated as AC, and dicumyl peroxide crosslinking agent is abbreviated as DCP. The phosphorus-containing silane coupling agent is P-Si-1, which contains hydrolyzable silane groups and phosphate ester structures, and the aminosilane is γ-aminopropyltriethoxysilane. The antioxidant is a compound antioxidant composed of hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1.

[0036] Example 1:

[0037] See Figure 1 As shown, the density of LDPE used in this embodiment is 0.921 g / cm³. 3 The melt flow rate is 2.0 g / 10 min; the vinyl acetate structural unit content in EVA is 18 wt%, and the melt flow rate is 2.5 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.875 g / cm³. 3 The melt flow rate was 2.0 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 1.2 wt%, the acid value was 12 mg KOH / g, and the melt flow rate was 3.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 3:1, the D50 particle size was 2.0 μm, and the D90 particle size was 6.0 μm; the D50 particle size of AlPi was 3.0 μm; the D50 particle size of MPP was 5.0 μm; the D50 particle size of zinc borate was 2.5 μm; the number average molecular weight of hydroxyl-containing silicone resin was 2500, and the hydroxyl value was 65 mg KOH / g; the D50 particle size of AC was 8.0 μm, and the decomposition peak temperature was 195℃.

[0038] According to the weight ratio, 100 parts of MgAl-LDH were added to an ethanol-water mixed solvent with a mass ratio of ethanol to water of 75:25 and a solid content of 20wt%. The pH was adjusted to 5.5. 2.75 parts of P-Si-1 were added, and the mixture was stirred at 65℃ for 1 h. Then, 1.5 parts of γ-aminopropyltriethoxysilane were added, and the mixture was stirred at 70℃ for 2 h. After the reaction was completed, the mixture was filtered, washed twice with an ethanol-water mixed solvent, washed once with ethanol, and dried at 90℃ for 6 h to obtain modified MgAl-LDH.

[0039] Weigh out 72 parts of LDPE, 18 parts of EVA, 10 parts of POE, 5.5 parts of PE-g-MAH, 29 parts of composite low-smoke halogen-free flame retardant, 10.5 parts of AC, 1.6 parts of DCP, 2.0 parts of zinc oxide, 0.7 parts of zinc stearate, 0.3 parts of antioxidant, and 0.5 parts of polyethylene wax; the composite low-smoke halogen-free flame retardant is composed of 10.73 parts of modified MgAl-LDH, 8.99 parts of AlPi, 4.06 parts of MPP, 3.19 parts of piperazine polyphosphate, 1.45 parts of zinc borate, and 0.58 parts of hydroxyl-containing silicone resin.

[0040] Modified MgAl-LDH and 2.75 parts of PE-g-MAH were added to a mixer and mixed at 120°C for 3 min. AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added and mixed at 125°C for 6 min. Granulation and drying were carried out until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0041] LDPE, EVA, POE, the remaining 2.75 parts of PE-g-MAH and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing; then AC, zinc oxide, zinc stearate, antioxidant and polyethylene wax were added; finally DCP was added; the barrel temperature was set to 108℃, the melt pressure was controlled at 10.1MPa, and the calender roll temperature was set to 45℃ to obtain an XPE foam masterbatch with a thickness of 1.60mm.

[0042] The XPE foam master sheet was pre-crosslinked at 162℃ for 2.5 min, and then continuously foamed at 208℃ for 3.0 min with a continuous foaming oven linear speed of 4.0 m / min. After cooling and shaping, it was cured at 70℃ for 4 h to obtain low-smoke halogen-free flame-retardant XPE foam.

[0043] Example 2:

[0044] See Figure 1 As shown, the density of LDPE used in this embodiment is 0.920 g / cm³. 3The melt flow rate is 1.8 g / 10 min; the vinyl acetate structural unit content in EVA is 18 wt%, and the melt flow rate is 2.2 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.875 g / cm³. 3 The melt flow rate was 2.0 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 1.2 wt%, the acid value was 12 mg KOH / g, and the melt flow rate was 3.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 3:1, the D50 particle size was 2.0 μm, and the D90 particle size was 6.0 μm; the D50 particle size of AlPi was 3.0 μm; the D50 particle size of MPP was 5.0 μm; the D50 particle size of zinc borate was 2.5 μm; the number average molecular weight of hydroxyl-containing silicone resin was 2500, and the hydroxyl value was 65 mg KOH / g; the D50 particle size of AC was 8.0 μm, and the decomposition peak temperature was 195℃.

[0045] According to the weight ratio, 100 parts of MgAl-LDH were added to an ethanol-water mixed solvent with a mass ratio of 75:25 and a solid content of 20wt%, and the pH was adjusted to 5.5. 3.0 parts of P-Si-1 were added, and the mixture was stirred at 65℃ for 1.5 h. Then 1.5 parts of γ-aminopropyltriethoxysilane were added, and the mixture was stirred at 70℃ for 2 h. After the reaction was completed, the mixture was filtered, washed twice with an ethanol-water mixed solvent, washed once with ethanol, and dried at 90℃ for 6 h to obtain modified MgAl-LDH.

[0046] Weigh out 72 parts of LDPE, 17 parts of EVA, 11 parts of POE, 6.0 parts of PE-g-MAH, 30 parts of composite low-smoke halogen-free flame retardant, 10.0 parts of AC, 1.7 parts of DCP, 2.0 parts of zinc oxide, 0.7 parts of zinc stearate, 0.3 parts of antioxidant, and 0.5 parts of polyethylene wax; the composite low-smoke halogen-free flame retardant is composed of 11.40 parts of modified MgAl-LDH, 9.30 parts of AlPi, 4.20 parts of MPP, 3.30 parts of piperazine polyphosphate, 1.20 parts of zinc borate, and 0.60 parts of hydroxyl-containing silicone resin.

[0047] Modified MgAl-LDH and 3.0 parts of PE-g-MAH were added to a mixer and mixed at 120°C for 3 min. AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added and mixed at 125°C for 6 min. Granulation and drying were carried out until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0048] LDPE, EVA, POE, the remaining 3.0 parts of PE-g-MAH and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing; then AC, zinc oxide, zinc stearate, antioxidant and polyethylene wax were added; finally DCP was added; the barrel temperature was set to 108℃, the melt pressure was controlled at 10.4MPa, and the calender roll temperature was set to 45℃ to obtain an XPE foam masterbatch with a thickness of 1.55mm.

[0049] The XPE foam master sheet was pre-crosslinked at 164℃ for 2.5 min, and then continuously foamed at 208℃ for 3.0 min with a continuous foaming oven linear speed of 4.0 m / min. After cooling and shaping, it was cured at 70℃ for 4 h to obtain low-smoke halogen-free flame-retardant XPE foam.

[0050] Example 3:

[0051] See Figure 1 As shown, the density of LDPE used in this embodiment is 0.925 g / cm³. 3 The melt flow rate is 0.8 g / 10 min; the vinyl acetate structural unit content in EVA is 12 wt%, and the melt flow rate is 1.0 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.885 g / cm³. 3 The melt flow rate was 0.8 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 0.6 wt%, the acid value was 6 mg KOH / g, and the melt flow rate was 1.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 2:1, the D50 particle size was 0.8 μm, and the D90 particle size was 3.2 μm; the D50 particle size of AlPi was 1.0 μm; the D50 particle size of MPP was 2.0 μm; the D50 particle size of zinc borate was 1.0 μm; the number average molecular weight of hydroxyl-containing silicone resin was 800, and the hydroxyl value was 120 mg KOH / g; the D50 particle size of AC was 4.0 μm, and the decomposition peak temperature was 180℃.

[0052] According to the weight ratio, 100 parts of MgAl-LDH were added to an ethanol-water mixed solvent with a mass ratio of ethanol to water of 60:40 and a solid content of 15wt%. The pH was adjusted to 5.0. 1.5 parts of P-Si-1 were added, and the mixture was stirred at 60℃ for 0.5 h. Then, 0.5 parts of γ-aminopropyltriethoxysilane were added, and the mixture was stirred at 60℃ for 1 h. After the reaction was completed, the mixture was filtered, washed twice with an ethanol-water mixed solvent, washed once with ethanol, and dried at 80℃ for 3 h to obtain modified MgAl-LDH.

[0053] Weigh out 78 parts of LDPE, 17 parts of EVA, 5 parts of POE, 4.0 parts of PE-g-MAH, 24 parts of composite low-smoke halogen-free flame retardant, 8.0 parts of AC, 1.1 parts of DCP, 1.0 part of zinc oxide, 0.3 parts of zinc stearate, 0.1 parts of antioxidant, and 0.2 parts of polyethylene wax. The composite low-smoke halogen-free flame retardant is composed of 8.16 parts of modified MgAl-LDH, 8.16 parts of AlPi, 3.84 parts of MPP, 2.16 parts of piperazine polyphosphate, 1.20 parts of zinc borate, and 0.48 parts of hydroxyl-containing silicone resin.

[0054] Modified MgAl-LDH and 2.0 parts of PE-g-MAH were added to a mixer and mixed at 110°C for 2 min. AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added and mixed at 115°C for 3 min. Granulation and drying were carried out until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0055] LDPE, EVA, POE, the remaining 2.0 parts of PE-g-MAH and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing; then AC, zinc oxide, zinc stearate, antioxidant and polyethylene wax were added; finally DCP was added; the barrel temperature was set to 102℃, the melt pressure was controlled at 8.4MPa, and the calender roll temperature was set to 38℃ to obtain an XPE foam masterbatch with a thickness of 1.45mm.

[0056] The XPE foam master sheet was pre-crosslinked at 150℃ for 1.0 min, and then continuously foamed at 195℃ for 1.5 min with a continuous foaming oven linear speed of 7.0 m / min. After cooling and shaping, it was cured at 60℃ for 3 h to obtain low-smoke halogen-free flame-retardant XPE foam.

[0057] Example 4:

[0058] See Figure 1 As shown, the density of LDPE used in this embodiment is 0.916 g / cm³. 3 The melt flow rate is 4.0 g / 10 min; the vinyl acetate structural unit content in EVA is 20 wt%, and the melt flow rate is 6.0 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.865 g / cm³. 3The melt flow rate was 5.0 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 1.8 wt%, the acid value was 18 mg KOH / g, and the melt flow rate was 8.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 3.5:1, the D50 particle size was 3.5 μm, and the D90 particle size was 8.0 μm; the D50 particle size of AlPi was 6.0 μm; the D50 particle size of MPP was 8.0 μm; the D50 particle size of zinc borate was 5.0 μm; the number average molecular weight of hydroxyl-containing silicone resin was 6000, and the hydroxyl value was 30 mg KOH / g; the D50 particle size of AC was 12.0 μm, and the decomposition peak temperature was 210℃.

[0059] According to the weight ratio, 100 parts of MgAl-LDH were added to an ethanol-water mixed solvent with a mass ratio of ethanol to water of 90:10 and a solid content of 30wt%. The pH was adjusted to 6.0. 4.0 parts of P-Si-1 were added, and the mixture was stirred at 75℃ for 2 hours. Then, 2.5 parts of γ-aminopropyltriethoxysilane were added, and the mixture was stirred at 85℃ for 4 hours. After the reaction was completed, the mixture was filtered, washed twice with an ethanol-water mixed solvent, washed once with ethanol, and dried at 105℃ for 10 hours to obtain modified MgAl-LDH.

[0060] Weigh out 65 parts of LDPE, 20 parts of EVA, 15 parts of POE, 7.0 parts of PE-g-MAH, 34 parts of composite low-smoke halogen-free flame retardant, 13.0 parts of AC, 2.2 parts of DCP, 3.0 parts of zinc oxide, 1.2 parts of zinc stearate, 0.5 parts of antioxidant, and 0.8 parts of polyethylene wax; the composite low-smoke halogen-free flame retardant is composed of 13.60 parts of modified MgAl-LDH, 9.52 parts of AlPi, 4.08 parts of MPP, 4.42 parts of piperazine polyphosphate, 1.36 parts of zinc borate, and 1.02 parts of hydroxyl-containing silicone resin.

[0061] Modified MgAl-LDH and 3.5 parts of PE-g-MAH were added to a mixer and mixed at 130°C for 5 min. AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added and mixed at 135°C for another 8 min. The mixture was then granulated and dried until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0062] LDPE, EVA, POE, the remaining 3.5 parts of PE-g-MAH and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing; then AC, zinc oxide, zinc stearate, antioxidant and polyethylene wax were added; finally DCP was added; the barrel temperature was set to 116℃, the melt pressure was controlled at 13.8MPa, and the calender roll temperature was set to 60℃ to obtain an XPE foam masterbatch with a thickness of 1.85mm.

[0063] The XPE foam master sheet was pre-crosslinked at 172℃ for 4.0 min, and then continuously foamed at 222℃ for 5.0 min with a continuous foaming oven linear speed of 2.4 m / min. After cooling and shaping, it was cured at 80℃ for 6 h to obtain low-smoke halogen-free flame-retardant XPE foam.

[0064] Comparative Example 1:

[0065] This comparative example illustrates the effect of unmodified MgAl-LDH replacing modified MgAl-LDH on foam properties.

[0066] The density of LDPE used in this comparative example is 0.920 g / cm³. 3 The melt flow rate is 1.8 g / 10 min; the vinyl acetate structural unit content in EVA is 18 wt%, and the melt flow rate is 2.2 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.875 g / cm³. 3 The melt flow rate was 2.0 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 1.2 wt%, the acid value was 12 mg KOH / g, and the melt flow rate was 3.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 3:1, the D50 particle size was 2.0 μm, and the D90 particle size was 6.0 μm; the D50 particle size of AlPi was 3.0 μm; the D50 particle size of MPP was 5.0 μm; the D50 particle size of zinc borate was 2.5 μm; the number average molecular weight of hydroxyl-containing silicone resin was 2500, and the hydroxyl value was 65 mg KOH / g; the D50 particle size of AC was 8.0 μm, and the decomposition peak temperature was 195℃.

[0067] MgAl-LDH was dried at 90℃ for 6 h without P-Si-1 and γ-aminopropyltriethoxysilane treatment.

[0068] Weigh out the following components by weight: 72 parts LDPE, 17 parts EVA, 11 parts POE, 6.0 parts PE-g-MAH, 30 parts composite flame retardant, 10.0 parts AC, 1.7 parts DCP, 2.0 parts zinc oxide, 0.7 parts zinc stearate, 0.3 parts antioxidant, and 0.5 parts polyethylene wax. The composite flame retardant consists of 11.40 parts unmodified MgAl-LDH, 9.30 parts AlPi, 4.20 parts MPP, 3.30 parts piperazine polyphosphate, 1.20 parts zinc borate, and 0.60 parts hydroxyl-containing silicone resin.

[0069] Unmodified MgAl-LDH was mixed with 3.0 parts of PE-g-MAH at 120℃ for 3 min; AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added, and the mixture was further mixed at 125℃ for 6 min. The mixture was then granulated and dried until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0070] LDPE, EVA, POE, the remaining 3.0 parts of PE-g-MAH and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing; then AC, zinc oxide, zinc stearate, antioxidant and polyethylene wax were added; finally DCP was added; the barrel temperature was set to 108℃, the melt pressure was controlled at 11.5MPa, and the calender roll temperature was set to 45℃ to obtain an XPE foam masterbatch with a thickness of 1.56mm.

[0071] XPE foam masterbatch was pre-crosslinked at 164℃ for 2.5 min, and then continuously foamed at 208℃ for 3.0 min with a continuous foaming oven linear speed of 4.0 m / min. After cooling and setting, it was cured at 70℃ for 4 h to obtain XPE foam.

[0072] Comparative Example 2:

[0073] This comparative example illustrates the effect of a total amount of composite low-smoke halogen-free flame retardant below 24 parts by weight on flame retardant and low-smoke performance.

[0074] The density of LDPE used in this comparative example is 0.920 g / cm³. 3 The melt flow rate is 1.8 g / 10 min; the vinyl acetate structural unit content in EVA is 18 wt%, and the melt flow rate is 2.2 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.875 g / cm³. 3 The melt flow rate was 2.0 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 1.2 wt%, the acid value was 12 mg KOH / g, and the melt flow rate was 3.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 3:1, the D50 particle size was 2.0 μm, and the D90 particle size was 6.0 μm; the D50 particle size of AlPi was 3.0 μm; the D50 particle size of MPP was 5.0 μm; the D50 particle size of zinc borate was 2.5 μm; the number average molecular weight of hydroxyl-containing silicone resin was 2500, and the hydroxyl value was 65 mg KOH / g; the D50 particle size of AC was 8.0 μm, and the decomposition peak temperature was 195℃.

[0075] Modified MgAl-LDH was prepared according to the method in Example 2.

[0076] Weigh out the following components by weight: 72 parts LDPE, 17 parts EVA, 11 parts POE, 6.0 parts PE-g-MAH, 20 parts composite low-smoke halogen-free flame retardant, 10.0 parts AC, 1.7 parts DCP, 2.0 parts zinc oxide, 0.7 parts zinc stearate, 0.3 parts antioxidant, and 0.5 parts polyethylene wax. The composite low-smoke halogen-free flame retardant is composed of 7.60 parts modified MgAl-LDH, 6.20 parts AlPi, 2.80 parts MPP, 2.20 parts piperazine polyphosphate, 0.80 parts zinc borate, and 0.40 parts hydroxyl-containing silicone resin.

[0077] Modified MgAl-LDH was mixed with 3.0 parts of PE-g-MAH at 120℃ for 3 min; AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added, and the mixture was further mixed at 125℃ for 6 min. The mixture was then granulated and dried until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0078] LDPE, EVA, POE, the remaining 3.0 parts of PE-g-MAH, and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing. Then, AC, zinc oxide, zinc stearate, antioxidants, and polyethylene wax were added. Finally, DCP was added. The barrel temperature was set to 108℃, the melt pressure was controlled at 9.1MPa, and the calender roll temperature was set to 45℃, resulting in an XPE foam masterbatch with a thickness of 1.50mm.

[0079] XPE foam masterbatch was pre-crosslinked at 164℃ for 2.5 min, and then continuously foamed at 208℃ for 3.0 min, with a continuous foaming oven linear speed of 4.0 m / min. After cooling and setting, it was cured at 70℃ for 4 h to obtain XPE foam.

[0080] Comparative Example 3:

[0081] This comparative example illustrates the effect of a total amount of composite low-smoke halogen-free flame retardant exceeding 34 parts by weight on the foam structure and mechanical properties.

[0082] The density of LDPE used in this comparative example is 0.920 g / cm³. 3 The melt flow rate is 1.8 g / 10 min; the vinyl acetate structural unit content in EVA is 18 wt%, and the melt flow rate is 2.2 g / 10 min; POE is an ethylene-octene copolymer elastomer with a density of 0.875 g / cm³. 3The melt flow rate was 2.0 g / 10 min; the maleic anhydride grafting rate of PE-g-MAH was 1.2 wt%, the acid value was 12 mg KOH / g, and the melt flow rate was 3.0 g / 10 min; the magnesium-aluminum molar ratio of MgAl-LDH was 3:1, the D50 particle size was 2.0 μm, and the D90 particle size was 6.0 μm; the D50 particle size of AlPi was 3.0 μm; the D50 particle size of MPP was 5.0 μm; the D50 particle size of zinc borate was 2.5 μm; the number average molecular weight of hydroxyl-containing silicone resin was 2500, and the hydroxyl value was 65 mg KOH / g; the D50 particle size of AC was 8.0 μm, and the decomposition peak temperature was 195℃.

[0083] Modified MgAl-LDH was prepared according to the method in Example 2.

[0084] According to weight, weigh out 72 parts LDPE, 17 parts EVA, 11 parts POE, 6.0 parts PE-g-MAH, 38 parts composite low-smoke halogen-free flame retardant, 10.0 parts AC, 1.7 parts DCP, 2.0 parts zinc oxide, 0.7 parts zinc stearate, 0.3 parts antioxidant, and 0.5 parts polyethylene wax. The composite low-smoke halogen-free flame retardant is composed of 14.44 parts modified MgAl-LDH, 11.78 parts AlPi, 5.32 parts MPP, 4.18 parts piperazine polyphosphate, 1.52 parts zinc borate, and 0.76 parts hydroxyl-containing silicone resin.

[0085] Modified MgAl-LDH was mixed with 3.0 parts of PE-g-MAH at 130℃ for 5 min; AlPi, MPP, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin were added, and the mixture was further mixed at 135℃ for 8 min. The mixture was then granulated and dried until the moisture content was less than 0.12 wt% to obtain flame retardant masterbatch.

[0086] LDPE, EVA, POE, the remaining 3.0 parts of PE-g-MAH and flame retardant masterbatch were added to a twin-screw extrusion calender for plasticizing and mixing; then AC, zinc oxide, zinc stearate, antioxidant and polyethylene wax were added; finally DCP was added; the barrel temperature was set to 118℃, the melt pressure was controlled at 16.7MPa, and the calender roll temperature was set to 60℃ to obtain an XPE foam masterbatch with a thickness of 1.72mm.

[0087] XPE foam masterbatch was pre-crosslinked at 164℃ for 2.5 min, and then continuously foamed at 208℃ for 3.0 min with a continuous foaming oven linear speed of 4.0 m / min. After cooling and setting, it was cured at 70℃ for 4 h to obtain XPE foam.

[0088] Comparative Example 4:

[0089] This comparative example is used to illustrate the differences between the melamine-formaldehyde-aluminum hypophosphite-based XPE flame retardant route and the system of this invention.

[0090] The density of LDPE used in this comparative example is 0.922 g / cm³. 3 The melt mass flow rate is 2.0 g / 10 min; the D50 particle size of AC is 8.0 μm and the decomposition peak temperature is 195 °C; DCP is dicumyl peroxide with an activity content of 98%.

[0091] According to the weight proportions, 500 parts of water were added to the reactor, the temperature was raised and stirred, and 130 parts of cyanuric acid and 30 parts of urea were added; when the material temperature reached 80℃, 100 parts of aluminum hypophosphite were added and stirring was continued; when the material temperature reached 90℃, 20 parts of ammonia water, 40 parts of formaldehyde solution and 160 parts of melamine were added, and the reaction was continued for 4 hours; after the reaction was completed, the mixture was filtered, dried, pulverized and sieved to obtain XPE special flame retardant.

[0092] Weigh out 80 parts of LDPE, 8 parts of the above-mentioned XPE-specific flame retardant, 12 parts of AC, 4.0 parts of DCP, and 3 parts of color masterbatch; add the above components to the extrusion equipment, mix and extrude and calender, set the barrel temperature to 110℃ and the calender roll temperature to 45℃, to obtain an XPE foam master sheet with a thickness of 1.50mm; pre-crosslink the master sheet at 170℃ for 3.0min, and then continuously foam at 210℃ for 3.0min, with a continuous foaming oven linear speed of 4.0m / min; after cooling and setting, cure at 70℃ for 4h to obtain XPE foam.

[0093] Comparative Example 5:

[0094] This comparative example is a commercially available flame-retardant XPE foam sample produced by Foshan Hongchen Packaging Materials Co., Ltd., with a nominal thickness of 5mm and a nominal density of 30kg / m³. 3 Flame-retardant XPE foam samples were cut and tested under the same conditioning and testing methods as in the example. This comparative example is not intended to infer the formulation composition, but only serves as a baseline for commercially available samples.

[0095] Test items and test conditions:

[0096] Before testing, all foam samples prepared in the examples and comparative examples were placed in an environment of 23±2℃ and 50±10% relative humidity for 24 hours. Three independent batches of each self-made sample were prepared; the point values ​​in the performance test experimental data table are the arithmetic mean of the test results of each batch.

[0097] Linear dimensions are tested according to GB / T 6342-1996: 5 specimens are cut for each sample, and the length, width and thickness of each specimen are measured at 3 locations, and the average thickness is recorded.

[0098] Apparent density was tested according to GB / T 6343-2009: sample size was 50mm × 50mm × actual thickness, with 5 samples per group.

[0099] Closed-cell rate is tested according to GB / T 10799-2008: Samples are taken from the middle of the foam, avoiding the edges and areas with obvious compaction on the surface, with 3 samples per group.

[0100] The average cell size was measured using optical microscopy image analysis: a cross-section was cut along the thickness direction of each sample, and three fields of view were photographed at 100x magnification. At least 100 cells were counted for each sample, and the average cell size was calculated using the equivalent circle diameter.

[0101] The gel content was tested using the xylene extraction method: approximately 0.300 g of foam sample was weighed and refluxed in xylene at 120℃ for 8 hours. After extraction, the sample was dried under vacuum at 80℃ to constant weight. For samples containing inorganic fillers, the ash content of the same formulation was used for deduction correction.

[0102] The oxygen index was tested according to GB / T 2406.2-2009: the samples were cut into 100mm×10mm×actual thickness, with 5 samples per group.

[0103] Horizontal combustion was tested according to FMVSS 302: the sample was cut into 356mm×100mm×actual thickness, 5 samples per group, and the combustion rate was recorded; if the sample self-extinguished after being removed from the flame, it was recorded as self-extinguishing.

[0104] Smoke density was tested according to GB / T 8627-2007: the sample was cut into 75mm×75mm×actual thickness, 3 samples were made in each group, and the smoke density level was recorded.

[0105] Compression set shall be tested in accordance with GB / T 6669-2008: the sample shall be cut into 50mm×50mm×25mm; for the sample with a thickness of less than 25mm, the same sample shall be stacked to 25mm, and the stacking direction shall be kept consistent; the test conditions shall be 50% compression, 70℃ treatment for 22h, and recovery for 30min before measurement.

[0106] Tensile strength and elongation at break were tested according to GB / T 6344-2008: the specimens were cut along the foam winding direction, with 5 specimens per group, and the tensile speed was 500 mm / min.

[0107] Thermal conductivity was tested according to GB / T 10294-2008: sample thickness was 5.0±0.5mm, and the average test temperature was 25℃.

[0108] Thermal aging performance was performed according to GB / T 7141-2008: the samples were placed in a 100℃ hot air aging chamber for 168 hours, and then placed in an environment of 23±2℃ for 24 hours after removal. The tensile strength retention rate and elongation at break retention rate were tested.

[0109] Water absorption rate was tested according to GB / T 1034-2008: the sample was soaked in water at 23℃ for 24 hours, then removed, wiped dry, and weighed.

[0110] The sound absorption coefficient was tested according to GB / T 18696.2-2002: the impedance tube transfer function method was used, the sample thickness was 5.0±0.5mm, the frequency range was 250~4000Hz, and the sound absorption coefficients at 1000Hz and 2000Hz were recorded.

[0111] Peel strength was tested according to GB / T 2792-2014: After corona treatment on one side of the foam, a 25μm thick PET film and pressure-sensitive adhesive layer were laminated to form a 25mm wide sample. After 24 hours, a 180° peel test was performed at a peel speed of 300mm / min, with 5 samples per group.

[0112] The test results are detailed in the following two tables:

[0113] sample Thickness / mm Density / kg·m⁻³ Closed-cell rate / % Average cell size / μm Gel content / % Oxygen Index / % FMVSS 302 combustion rate / mm·min⁻¹ Smoke density level Compression permanent deformation / % Tensile strength / MPa Elongation at break / % Example 1 5.2 48 93.4 168 47.8 30.4 42 63 17.8 0.86 122 Example 2 5.1 46 94.6 152 49.2 31.2 35 57 15.9 0.91 135 Example 3 4.8 61 90.1 214 36.5 28.5 58 72 21.5 0.82 118 Example 4 5.5 55 91.7 185 58.4 31.8 32 61 24.2 0.76 96 Comparative Example 1 5.0 54 88.2 238 48.5 27.6 76 82 27.5 0.68 82 Comparative Example 2 5.4 43 92.8 176 48.7 25.9 112 95 18.6 0.94 142 Comparative Example 3 4.4 72 84.9 305 50.1 32.0 30 67 35.8 0.55 52 Comparative Example 4 5.2 51 86.5 265 61.8 27.8 68 88 31.2 0.62 70 Comparative Example 5 5.0 32 89.0 295 43.0 26.8 55 98 28.0 0.50 90

[0114] sample Thermal conductivity / W·m⁻¹·K⁻¹ Tensile strength retention rate at 100℃ for 168 hours / % Elongation at break retention rate (%) after 100℃×168h 24h water absorption rate / % 1000Hz sound absorption coefficient 2000Hz sound absorption coefficient PET composite 180° peel strength / N·25mm⁻¹ Example 1 0.043 88 84 0.42 0.18 0.31 8.6 Example 2 0.041 91 88 0.38 0.20 0.34 9.4 Example 3 0.045 83 79 0.48 0.16 0.27 7.1 Example 4 0.046 86 80 0.44 0.17 0.29 7.5 Comparative Example 1 0.047 76 70 0.62 0.13 0.23 5.6 Comparative Example 2 0.040 89 86 0.41 0.19 0.33 9.1 Comparative Example 3 0.052 71 64 0.71 0.11 0.19 4.8 Comparative Example 4 0.050 74 68 0.58 0.12 0.22 5.2 Comparative Example 5 0.044 78 73 0.80 0.14 0.26 5.0

[0115] Analysis of experimental results:

[0116] Examples 1 to 4 all successfully formed closed-cell XPE foams with a thickness of 4.8–5.5 mm, a closed-cell rate of not less than 90.1%, an average cell size between 152 and 214 μm, and a gel content between 36.5% and 58.4%. These results demonstrate that, within the defined ranges of ternary polyolefin matrix, composite low-smoke halogen-free flame retardant, maleic anhydride-grafted polyethylene compatibilizer, foaming agent, and crosslinking agent, continuously foamed closed-cell foams can be obtained.

[0117] Example 2 exhibited a closed-cell rate of 94.6%, an average cell size of 152 μm, a gel content of 49.2%, an oxygen index of 31.2%, a horizontal combustion rate of 35 mm / min on FMVSS 302, a smoke density rating of 57, a compression set of 15.9%, a tensile strength of 0.91 MPa, an elongation at break of 135%, and a thermal conductivity of 0.041 W·m. -1 ·K -1 The PET composite exhibits a 180° peel strength of 9.4 N / 25 mm. Example 2 demonstrates a good overall balance between cell structure, flame retardancy and low smoke, compression recovery, mechanical properties, thermal insulation, and composite processability, and can be considered a preferred embodiment.

[0118] Example 3 contained 24 parts of a composite low-smoke halogen-free flame retardant, 4 parts of PE-g-MAH, 8 parts of AC, and 1.1 parts of DCP. The oxygen index of Example 3 was 28.5%, the burning rate was 58 mm / min, and the smoke density rating was 72, both weaker than Example 2. Its closed-cell rate was 90.1%, and the average cell size was 214 μm, also weaker than Example 2. These results indicate that usable foam can still be formed at the lower boundary, but the flame retardancy, low smoke, and cell uniformity are inferior to the preferred embodiment.

[0119] Example 4 is located at the high-end edge, with 34 parts of a composite low-smoke halogen-free flame retardant, 7 parts of PE-g-MAH, 13 parts of AC, and 2.2 parts of DCP. Example 4 has an oxygen index of 31.8% and a burning rate of 32 mm / min, exhibiting good flame retardant performance; however, its compression set is 24.2%, elongation at break is 96%, and its thermal conductivity is 0.046 W·m. -1 ·K -1 The PET composite exhibited a 180° peel strength of 7.5 N / 25 mm, which was weaker than that of Example 2. This result indicates that the high-end boundary is beneficial for flame retardancy, but higher filler content and cross-linking degree can make the foam stiffer and reduce flexibility, compression recovery, and composite interface stability.

[0120] Compared to Example 2, Comparative Example 1 only replaced the modified MgAl-LDH with unmodified MgAl-LDH. The closed-cell ratio of Comparative Example 1 decreased from 94.6% in Example 2 to 88.2%, the average cell size increased from 152 μm to 238 μm, the smoke density rating increased from 57 to 82, the combustion speed increased from 35 mm / min to 76 mm / min, the compression set increased from 15.9% to 27.5%, and the 180° peel strength of the PET composite decreased from 9.4 N / 25 mm to 5.6 N / 25 mm. These results demonstrate that surface modification of MgAl-LDH can improve its dispersion and interfacial bonding in polyolefin systems, thereby improving cell stability, low smoke effect, compression recovery, and composite processability.

[0121] Compared to Example 2, Comparative Example 2 reduced the total amount of composite low-smoke halogen-free flame retardant to 20 parts, and its density was 43 kg / m³. 3 The closed-cell rate was 92.8%, the average cell size was 176 μm, the tensile strength was 0.94 MPa, and the elongation at break was 142%, indicating acceptable foaming structure and mechanical properties. However, its oxygen index decreased to 25.9%, the burning rate increased to 112 mm / min, and the smoke density rating increased to 95. These results indicate that when the composite low-smoke halogen-free flame retardant content is below 24 parts, its flame retardant and low-smoke capabilities are insufficient, making it difficult to support the low-smoke halogen-free flame retardant effect of this invention.

[0122] Compared with Example 2, Comparative Example 3 increased the total amount of composite low-smoke halogen-free flame retardant to 38 parts. The oxygen index of Comparative Example 3 was 32.0%, and the burning speed was 30 mm / min, but the closed-cell rate decreased to 84.9%, the average cell size increased to 305 μm, and the density increased to 72 kg / m³. 3 Compression set increased to 35.8%, elongation at break decreased to 52%, and thermal conductivity increased to 0.052 W·m. -1 ·K -1 The 180° peel strength of PET composites decreased to 4.8 N / 25 mm. This result indicates that although excessive flame retardant can maintain a high oxygen index, it significantly damages the cell structure, compression recovery, flexibility, and composite processability. Therefore, setting an upper limit for composite low-smoke halogen-free flame retardants is necessary.

[0123] Comparative Example 4 exhibited an oxygen index of 27.8%, a burning rate of 68 mm / min, a smoke density rating of 88, a closed-cell rate of 86.5%, an average cell size of 265 μm, a compression set of 31.2%, and an elongation at break of 70%. Compared to Example 2, Comparative Example 4 was weaker in terms of low smoke, closed-cell structure, compression recovery, and flexibility. These results indicate that the present invention does not simply employ a melamine-formaldehyde-aluminum hypophosphite-based XPE flame retardant route, but rather achieves comprehensive improvement through the combination of external surface modification with MgAl-LDH, a six-component composite low-smoke halogen-free flame retardant system, a PE-g-MAH compatibilizer, and a continuous foaming window.

[0124] Comparative Example 5 is a commercially available flame-retardant XPE sample with an oxygen index of 26.8%, a smoke density rating of 98, an average cell size of 295 μm, a compression set of 28.0%, a tensile strength of 0.50 MPa, and a 180° peel strength of 5.0 N / 25 mm for the PET composite. This comparative example is not used to infer commercial product formulations but only serves as a baseline for commercially available materials. Compared to this, Example 2 exhibits better overall performance in terms of low smoke, cell uniformity, compression recovery, tensile strength, heat retention, and peel strength.

[0125] In summary, the comparison between the examples and the comparative examples verifies the following beneficial effects: the phosphate ester-siloxane modification of MgAl-LDH on the outer surface is beneficial to improving the dispersibility and cell stability of the flame retardant system; the six-component composite low-smoke halogen-free flame retardant system can balance flame retardancy, low smoke, and foaming processability within the range of 24 to 34 parts; the PE-g-MAH compatibilizer and flame retardant masterbatch process is beneficial to reducing filler agglomeration; the pre-crosslinking and continuous foaming process window is beneficial to obtaining low-smoke halogen-free flame retardant XPE foam with matching density, closed-cell rate, cell size, and gel content.

[0126] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

[0127] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described above. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-smoke, halogen-free, flame-retardant XPE foam, characterized in that, Formed by chemical cross-linking and foaming of raw materials comprising the following components, wherein the raw materials, based on 100 parts by weight of a polyolefin matrix resin, include: 100 parts by weight of polyolefin matrix resin, 4-7 parts by weight of maleic anhydride grafted polyethylene compatibilizer, 24-34 parts by weight of composite low-smoke halogen-free flame retardant, 8-13 parts by weight of azodicarbonamide foaming agent, 1.1-2.2 parts by weight of dicumyl peroxide crosslinking agent, 1-3 parts by weight of zinc oxide, 0.3-1.2 parts by weight of zinc stearate, 0.1-0.5 parts by weight of antioxidant, and 0.2-0.8 parts by weight of polyethylene wax; The polyolefin matrix resin is composed of low-density polyethylene, ethylene-vinyl acetate copolymer and polyolefin elastomer, wherein the low-density polyethylene is 65-78 parts by weight, the ethylene-vinyl acetate copolymer is 12-22 parts by weight, and the polyolefin elastomer is 5-15 parts by weight, totaling 100 parts by weight. The composite low-smoke halogen-free flame retardant is composed of phosphate ester-siloxane modified magnesium aluminum hydrotalcite, aluminum diethylphosphinate, melamine polyphosphate, piperazine polyphosphate, zinc borate, and hydroxyl-containing silicone resin.

2. The low-smoke halogen-free flame-retardant XPE foam according to claim 1, characterized in that, Based on the mass of the composite low-smoke halogen-free flame retardant as 100wt%, the outer surface phosphate ester-siloxane modified magnesium aluminum hydrotalcite is 34-40wt%, diethylphosphinate aluminum is 28-34wt%, melamine polyphosphate is 12-16wt%, piperazine polyphosphate is 9-13wt%, zinc borate is 4-7wt%, and hydroxyl-containing silicone resin is 2-5wt%.

3. The low-smoke halogen-free flame-retardant XPE foam according to claim 1, characterized in that, The phosphate-siloxane modified magnesium aluminum hydrotalcite on the outer surface is obtained by surface treatment of magnesium aluminum hydrotalcite, phosphorus-containing silane coupling agent and γ-aminopropyltriethoxysilane in a mass ratio of 100:1.5-4.0:0.5-2.

5.

4. The low-smoke halogen-free flame-retardant XPE foam according to claim 1, characterized in that, The low-smoke halogen-free flame-retardant XPE foam has a thickness of 1.0–12 mm and a foaming ratio of 8–28 times; the antioxidant is a combination of hindered phenolic antioxidants and phosphite antioxidants, with a mass ratio of 1:0.5–2; the azodicarbonamide foaming agent has a D50 particle size of 4–12 μm and a decomposition peak temperature of 180–210 °C.

5. A low-smoke halogen-free flame-retardant XPE foam according to any one of claims 1 to 4, characterized in that, The low-smoke halogen-free flame-retardant XPE foam is suitable for XPE sheets, rolls or composite foams that require low-smoke halogen-free flame retardancy, closed-cell insulation and composite processability.

6. A method for preparing low-smoke halogen-free flame-retardant XPE foam, characterized in that, Includes the following steps: S1, External Surface Modification: Magnesium aluminum hydrotalcite is dispersed in an ethanol-water mixed solvent, a phosphorus-containing silane coupling agent is added for the first surface treatment, and then γ-aminopropyltriethoxysilane is added for the second surface treatment. After filtration, washing and drying, phosphate ester-siloxane modified magnesium aluminum hydrotalcite is obtained. S2, Preparation of flame retardant masterbatch: The magnesium aluminum hydrotalcite with phosphate ester-siloxane modified on the outer surface obtained in step S1 is mixed with a portion of maleic anhydride grafted polyethylene compatibilizer, and then aluminum diethylphosphinate, melamine polyphosphate, piperazine polyphosphate, zinc borate and hydroxyl-containing silicone resin are added and mixed again, granulated, to obtain flame retardant masterbatch. S3, Preparation of XPE foam masterbatch: Low-density polyethylene, ethylene-vinyl acetate copolymer, polyolefin elastomer, remaining maleic anhydride grafted polyethylene compatibilizer and flame retardant masterbatch obtained in step S2 are added to an extrusion device for plasticizing and mixing. Then, azodicarbonamide foaming agent, zinc oxide, zinc stearate, antioxidant and polyethylene wax are added. Finally, dicumyl peroxide crosslinking agent is added, and the mixture is extruded and calendered to obtain XPE foam masterbatch. S4, Pre-crosslinking and continuous foaming: The XPE foam master sheet obtained in step S3 is pre-crosslinked at 150-172°C for 1-4 min, then continuously foamed at 195-222°C for 1-5 min, and cooled and shaped to obtain the low-smoke halogen-free flame-retardant XPE foam.

7. The method for preparing low-smoke halogen-free flame-retardant XPE foam according to claim 6, characterized in that, In step S1, the mass ratio of ethanol to water in the ethanol-water mixed solvent is 60-90:10-40, the solid content of magnesium aluminum hydrotalcite in the ethanol-water mixed solvent is 10-35 wt%, and the pH of the system is 4.5-6.5; the mass ratio of magnesium aluminum hydrotalcite, phosphorus-containing silane coupling agent, and γ-aminopropyltriethoxysilane is 100:1.5-4.0:0.5-2.5; the temperature of the first surface treatment is 50-75℃, and the time is 0.5-2h; the temperature of the second surface treatment is 55-85℃, and the time is 1-4h; the drying temperature is 80-105℃, and the drying time is 3-10h.

8. The method for preparing low-smoke halogen-free flame-retardant XPE foam according to claim 6, characterized in that, In step S2, the phosphate-siloxane modified magnesium aluminum hydrotalcite with an outer surface is first mixed with a portion of maleic anhydride-grafted polyethylene compatibilizer at 110–130°C for 2–5 min. Then, aluminum diethylphosphonate, melamine polyphosphate, piperazine polyphosphate, zinc borate, and hydroxyl-containing silicone resin are added, and the mixture is further mixed at 115–140°C for 3–8 min. After granulation, the moisture content of the flame retardant masterbatch is controlled to be below 0.12 wt%.

9. The method for preparing low-smoke halogen-free flame-retardant XPE foam according to claim 6, characterized in that, In step S3, the barrel temperature of the extrusion equipment is 95-120℃, the melt pressure is 6-15MPa, the calender roll temperature is 30-65℃, and the thickness of the XPE foam masterbatch is 0.5-5.0mm; in step S4, the linear speed of the continuous foaming furnace is 2-8m / min.

10. The method for preparing low-smoke halogen-free flame-retardant XPE foam according to claim 6, characterized in that, After foaming, the product undergoes curing at 50–90°C for 2–8 hours, followed by one or more post-treatments, including cutting, winding, slicing, embossing, hot pressing, adhesive bonding, corona treatment, or plasma treatment.